2007
DOI: 10.1038/sj.bjp.0707251
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and pathological changes in the redox state of human serum albumin critically influence its binding properties

Abstract: Binding and transport of a number of endogenous and exogenous compounds is an important function of the main plasma protein, albumin. In vivo and in vitro, albumin may be oxidatively modified in different ways with different agents at different sites. These modifications have various consequences on the physiological functions of albumin. Diabetes mellitus, liver diseases and nephropathy are just a few examples of disorders in which oxidative stress is involved and altered albumin functions have been described… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
270
1
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(287 citation statements)
references
References 140 publications
(150 reference statements)
6
270
1
10
Order By: Relevance
“…However, though the effects of high levels of total plasma NEFAs have been studied (10,11,61), the putative deterioration in the NEFA binding capacity of albumin was not addressed in a systematic way. In previous studies, it was reported that oxidative stress and glycation caused conformational changes in albumin structure (14,29,62) with possible effects in vitro on platelet function (17,63,64). The novelty of the current study is the demonstration that glycation probably impairs the binding properties of albumin of patients with T2D.…”
Section: Discussionmentioning
confidence: 69%
“…However, though the effects of high levels of total plasma NEFAs have been studied (10,11,61), the putative deterioration in the NEFA binding capacity of albumin was not addressed in a systematic way. In previous studies, it was reported that oxidative stress and glycation caused conformational changes in albumin structure (14,29,62) with possible effects in vitro on platelet function (17,63,64). The novelty of the current study is the demonstration that glycation probably impairs the binding properties of albumin of patients with T2D.…”
Section: Discussionmentioning
confidence: 69%
“…[26] Serum albumin plays a vital role in the binding of drugs, hormones, iron and free fatty acids, and reduced levels may contribute to cognitive impairment resulting from toxicity. [27] Albumin also inhibits the formation of amyloid beta-peptide fibrils, [28] and low levels of albumin in the brain and cerebrospinal fluid may therefore lead to increased Alzheimer's type pathology. [29] While serum albumin levels may lead to cognitive impairment, reverse causality is also possible, and cognitive impairment may result in lowered serum albumin.…”
Section: Discussionmentioning
confidence: 99%
“…1͒, comes from two aromatic residues of tyrosine ͑Tyr͒ and tryptophan ͑Trp͒ located in subdomain IIIA and 214th residue of subdomain IIA, respectively. 15,16 No other fluorescence emission is observed other than a weak Raman signal from water at around 3400 cm −1 with respect to the excitation wavelength, which was always present and could be, if needed, digitally removed from those spectra. Next, the albumin solution was treated with leadcontaining solution starting from 1 pM ͑10 −12 M͒ concentration.…”
mentioning
confidence: 99%